Original paperThree-dimensional dosimetric considerations from different point A definitions in cervical cancer low-dose-rate brachytherapy - Zhang, Miao; Chen, Ting; Kim, Leonard H.; Nelson, Carl; Gabel, Molly; Narra, Venkat; Haffty, Bruce; Yue, Ning J. (Journal of Contemporary Brachytherapy, 2013)
Purpose : To investigate the dosimetric difference due to the different point A definitions in cervical cancer low-dose-rate (LDR) intracavitary brachytherapy. Material and methods: Twenty CT-based LDR brachytherapy plans of 11 cervical patients were retrospectively reviewed. Two plans with point As following the modified Manchester system which defines point A being 2 cm superior to the cervical os along the tandem and 2 cm lateral (A os ), and the American Brachytherapy Society (ABS) guideline definition in which the point A is 2 cm superior to the vaginal fornices instead of os (A ovoid ) were generated. Using the same source strength, two plans prescribed the same dose to A os and A ovoid . Dosimetric differences between plans including point A dose rate, treatment volume encompassed by the prescription isodose line (TV), and dose rate of 2 cc of the rectum and bladder to the prescription dose were measured. Results : On average A ovoid was 8.9 mm superior to A os along the tandem direction with a standard deviation of 5.4 mm. With the same source strength and arrangement, A os dose rate was 19% higher than A ovoid dose rate. The average TV(A ovoid ) was 118.0 cc, which was 30% more than the average TV(A os ) of 93.0 cc. D 2cc /D(Aprescribe) increased from 51% to 60% for rectum, and increased from 89% and 106% for bladder, if the prescription point changed from A os to A ovoid . Conclusions : Different point A definitions lead to significant dose differences. Careful consideration should be given when changing practice from one point A definition to another, to ensure dosimetric and clinical equivalency from the previous clinical experiences.